Implementasi Kebijakan Padat Karya Tunai (PKT) pada Masyarakat Miskin di Desa Lebih, Gianyar - Anak Agung Gde Rai Budiasa; A. A. Gde Raka; I Made Mardika (Universitas Warmadewa, 2019)
Abstract Cash intensive work (PKT) is an activity of empowering poor families that is productive by utilizing appropriate resources and technology in reducing poverty, increasing income, and reducing stunting, through self-management, prioritizing local workforce and materials. Lebih Village as a research object with consideration, namely as a tourism area and is near to the government center. This research is entitled